The Impact of the Voting System in the Security Council on the Effectiveness of its Role in Resolving Conflicts Affecting International Peace and Security, the Syrian Crisis - Anoud Abdulrahman Al-Habashneh (Zanco Journal of Human Sciences, 2025)
The study aimed to analyze the voting system in the Security Council to resolve disputes affecting international peace and security towards the Syrian crisis during the period (2011-2023), and to clarify the nature of the Council’s powers in maintaining international security, and to identify the dimensions of the conflict between international powers and their impact on its role in Syria. In order to answer the study’s questions, the study will use the descriptive analytical approach and the legal approach. The study shows that political interests have a great impact on the Council’s role in resolving international crises, including the Syrian crisis, which works to use the veto right to achieve its interests in Syria, and that the limited role of the Security Council in addressing the issues presented to it is clearly embodied in the Syrian crisis. How can it be reasonable for the Security Council to be unable to resolve this crisis for more than a decade, if it actually has the ability and capacity to end international armed crises and conflicts? The Syrian crisis and how the Security Council dealt with it made many expect this crisis to continue indefinitely. Based on the results of the study, it recommends that the criteria and controls by which countries are selected for membership in the Security Council should be reformulated, such that the number of seats in the Security Council be twenty.